Applying numerical method to understand the effect of climate change on the salinity intrusion in Ca River Basin, Vietnam - Q. T. Doan; N. C. Don; Y. C. Chen; P. K. Mishra (International Association of Lowland Technology, 2015)
Climate change and global warming are expected to have significant effects on water resources planning and management, especially in estuary areas. One-dimensional MIKE 11 model was established and applied to the Ca River Basin. The model was calibrated and validated with available hydrographical measured data in 1996, 1997, 1999 and 2000. The results of calibration and validation water level showed a high conformity about phase and water amplitude between calculated and observed data. The effect of global warming on salinity intrusion in estuarine areas was simulated in this study. The results of current state scenario (2010) and climate change scenario in 2020, 2050 and 2100 showed an overall effect of salinity intrusion process on precipitation and sea level rise. The distance of salinity intrusion in the river is increasing and this could be detrimental to the economic development, especially for the agriculture sector. The rise in sea level due to global warming will not significantly affect the situation of salinity intrusion for Ca River in 2020. However, comparing the results of scenario (2100) and the current state scenario (2010), the impact on salinity intrusion process in the Lam-Ca River system is found to be significant.